2010
DOI: 10.1007/s13420-010-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons exhibit higher accuracy for chosen memory tests than for forced memory tests in duration matching-to-sample

Abstract: Following training to match 2-and 8-sec durations of feederlight to red and green comparisons with a 0-sec baseline delay, pigeons were allowed to choose to take a memory test or to escape the memory test. The effects of sample omission, increases in retention interval, and variation in trial spacing on selection of the escape option and accuracy were studied. During initial testing, escaping the test did not increase as the task became more difficult, and there was no difference in accuracy between chosen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 25 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…The dolphins seemed to choose this option when they had a bigger probability of failing the task (Smith et al, 1995). Similar results were found in rats and pigeons (Adams and Santi, 2011;Foote and Crystal, 2007). However, it is believed that metacognition requires self-reflective consciousness and certain scientists question the existence of such capacities in non-primates, because more simple behavioural principles may also explain the observed behaviour, such as information seeking behaviour (Foote and Crystal, 2012;Kirk et al, 2014;Smith et al, 2008).…”
Section: Box 12 Cognitive Abilities Of Animalssupporting
confidence: 66%
“…The dolphins seemed to choose this option when they had a bigger probability of failing the task (Smith et al, 1995). Similar results were found in rats and pigeons (Adams and Santi, 2011;Foote and Crystal, 2007). However, it is believed that metacognition requires self-reflective consciousness and certain scientists question the existence of such capacities in non-primates, because more simple behavioural principles may also explain the observed behaviour, such as information seeking behaviour (Foote and Crystal, 2012;Kirk et al, 2014;Smith et al, 2008).…”
Section: Box 12 Cognitive Abilities Of Animalssupporting
confidence: 66%
“…Thus, in Experiment 1a, we found no evidence of prospective information-seeking in rats. Adams and Santi (2011) reported that extensive training eventually resulted in pigeons responding adaptively in relation to their memory states, whereas such responses were not observed during initial testing. Would more extensive training enhance effective information-seeking behavior in rats?…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches are based on the assumption that animals have a form of metacognition that allows them to access the reliability of their memory traces in some way. This has been shown in, e.g., macaques ( Macaca mulatta ; Hampton 2001 ), large-billed crows ( Corvus macrorhynchos ; Goto and Watanabe 2012 ), pigeons ( Columba livia ; Adams and Santi 2011 ), and even bees ( Apis mellifera ; Perry and Barron 2013 ). Arbilly and Lotem ( 2017 ) have made a strong argument for why such an ability does not need to involve highly complex cognition.…”
Section: Introductionmentioning
confidence: 80%